COGNITIVE DYSONANCE IN THE PROBLEM FIELD OF PHYSICAL EDUCATION - Вржесневський, I.; Лукашова, I.; Совгіря, T.; Пахомов, В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The given work deals with issues of pedagogy and psychology, which are associated with negative trends in physical health and physical training of student youth. Among the factors that influence the prospects of the physical condition and life of students are those that are traditionally ignored in modern pedagogical constructs (laziness, phobia, spiritual quasi-reality, etc.). The influence of these factors is reflected in the confrontation of various kinds of cognition, that is, in cognitive dissonance. Cognitive dissonance in the field of physical effort and motor activity has specific research features which can be a prerequisite for the formation of a successful positive motivation of students for occupations (including independent) physical education. The purpose of the article is to determine possible manifestations and consequences of cognitive dissonance that arise from students in relation with physical activity and exercises in the problem field of physical education. The authors proposed a number of points and assumptions about the definition of cognitive dissonance in this area, namely: – cognitive dissonance in relation to a person before physical education is usually the result of a collision of not only two but several cognitions; – in this cognitive dissonance there is a place not only for the theoretical and empirical, but also for "body knowledge"; – body knowledge as a product of physical activity that has a tendency at the unconscious level to correct the declarative decisions of the conscious; – the hierarchy of conscious and unconscious in relation to a person to the physical conditions of his own body does not have clearly defined boundaries; – the most widespread decision (choice) of the indicated cognitive dissonance is the "postponement of action". The given theses have partial confirmation in the results of the conducted research (questionnaires), partly require further research. The findings of the study include the assertion that one conscious understanding of the need for regular balanced exercises physical education to create a stable positive motivation is not enough without the relevant motor experience